Rediscovering Islamic values and elements in P. Ramlee’s film using Islamic epistemology-based data analysis - Ismail @ Ahmad, Muslim; Yusoff, Zulkarnain; Ismail, Mohd Nasir; Ismail, Mohd Saufi (Universiti Teknologi MARA, Kelantan, 2018)
Undoubtedly, P. Ramlee’s film is the national treasure of, not only the Malay film industry, but also the treasure of Malaysian hearts and minds. All generations of Malay, Chinese and Indian adore P. Ramlee’s film though the films were made decades ago with whatever technology available at that time. Intellectuals and scholars such as Afifi al-Akiti and Kazim Elias have categorically contributed P. Ramlee films success to his cunning crafty ideas and aspiration in incorporating Islamic values in film making. In this research, selected scenes from three of Ramlee films, Ali Baba Bujang Lapok (1961), Tiga Abdul (1964) and Ahmad Albab (1968) are qualitatively processed based on pre-defined Islamic values. The Islamic Epistemology Based Data Analysis is then applied in which verses of the Quran is retrieved based on potential keyword. The main focus is to extract potential reference points made in the films as Al-Akiti (2013).